Variable Sampling Period Filter PLL for Distorted Three-Phase Systems - Carugati, I.; Maestri, S.; Donato, P. G.; Carrica, D.; Benedetti, M. (IEEE transactions on power electronics, 2012)
This paper proposes a novel variable sampling period filter phase-locked loop (VSPF-PLL) for use in the general area of three-phase systems. It is based on the concept of variable sampling period, which allows to automatically adjust the sampling frequency to be N PLL times the line frequency. Conventional three-phase PLL are based on synchronous reference frames (SRFs) to estimate the phase error between the PLL and the input signals. However, SRF transform fail when the voltage waveforms are distorted. In this paper, a sliding-Goertzel-transform- based filter is used in the loop to reject disturbances, such as unbalanced voltage and harmonics. It allows to detect the positive sequence present in the systems without errors. Characteristics of VSPF-PLL, including its mathematical model as well as steady state and dynamic responses, are discussed in this paper. The method is implemented in a DSP and tested using typical disturbances, such as frequency steps, unbalances, harmonics, saturation, and line-to-ground fault. Comparative simulations are performed between the proposed VSPF-PLL and some of the most common three-phase PLL described in the literature. Advantages of the proposed system over the methods analyzed are also discussed. Structural simplicity, robustness, and harmonics rejection are other attractive features offered by the proposed system.